Correction to: Benefits and harm of systemic steroids for short‐ and long‐term use in rhinitis and rhinosinusitis: an EAACI position paper. Issue 1 (28th September 2020) - Hox, Valerie; Lourijsen, Evelijn; Jordens, Arnout; Aasbjerg, Kristian; Agache, Ioana; Alobid, Isam; Bachert, Claus; Boussery, Koen; Campo, Paloma; Fokkens, Wytske; Hellings, Peter; Hopkins, Claire; et al.
Abstract : An amendment to this paper has been published and can be accessed via the original article.